La azarosa vida de un naturalista sensible : Charles Darwin (1809-1882) - Schnack, Juan Alberto (2018)
Biographical and scientific aspects concerning the most important naturalist of the XIXth century, Charles Darwin (1809-1882), are analyzed regarding the most significant events of his life and work dealing with the process of organic evolution and the mechanism of natural selection.